Takbiran Carnival Tradition in Welcoming Eid Al-Fitr During a Pandemic - Anhar Syafiq Rusdianto; Busro Busro (UIN Sunan Gunung Djati Bandung, 2022)
Lebaran is the moment that Muslims in the world have been waiting for, they are waiting for the holiday that occurs only twice this year. As a country that has a variety of cultures, of course there is a uniqueness of each in an effort to enliven the coming of Eid. One of them is the Takbiran Carnival in Demak, Central Java. This Takbiran Carnival has become something that is inherent for the people of Demak and its surroundings, because this tradition will definitely be a place for people to gather and conduct a carnival by traveling around the streets of their respective villages while parading large dolls with various characters or shapes accompanied by a sound system to sing. takbir sentence. In the last two years the Takbiran Carnival has been canceled by the local government due to the Covid-19 Virus. Takbiran Carnival is an activity that involves quite a lot of people and also attracts the attention of many pairs of eyes. Crowd is one of the keys to the success of this tradition. The purpose of this study is to find out how the mechanism of implementing the Takbiran carnival tradition in the covid-19 pandemic, especially the traditions that exist when approaching the Eid al-Fitr, This research method uses a qualitative type and library research approach and literature review, this Takbiran Carnival is carried out right on the eve of Eid , not infrequently this carnival also meets the main streets and meets each other then the streets will be very crowded and tend to be jammed because of the hectic takbiran carnival. This Takbiran Carnival tradition is the center of attention especially for immigrants or travelers returning to their hometowns around Demak-Kudus, Central Java. It is hoped that this research will provide additional insight in the academic field and can be used as reading material for the general public.